PERBANDINGAN SISTEM DISTILASI ASAP CAIR TUNGGAL PIPA DENGAN MULTI PIPA TERHADAP KAPASITAS PRODUKSI ALAT PENYULINGAN ASAP CAIR - Ela Davera Ningsih Harahap; Andriyono Andriyono; Yus Witdarko (Faculty of Agriculture, Musamus University, 2021)
This study aims to compare the production capacity of single-pipe condenser liquid smoke distillation with the multi-pipe condenser. The liquid smoke distillation equipment in this study was single pipe and multi-pipe with specifications for combustion tubes of 135 cm x 60 cm, condenser pipe length of 110 cm, a cooling tube of 60 cm x 60 cm. This tool consists of three main components, namely the biomass combustion chamber; water container for the cooling process; and condensation pipe. The samples used were rice husk, coconut shell, and sawdust. The variation of the burning time is 5 hours, 10 hours, and 15 hours, but the coconut shell is only for 10 hours of burning. The results of the tool test after 15 hours showed that the average liquid smoke in a single pipe system from coconut shell, rice husk, and sawdust in the sequence was: 2.016 ml; 2,130 ml; and 2,133.3 ml. Meanwhile, the average liquid smoke produced using a multi-pipe system from each biomass is 3,096.6 ml; 4.150 ml; and 3,600 ml. Based on the resulting liquid smoke production, the distillation apparatus with a multi-pipe system is more efficient than a single-pipe system.